Assessment of physical activity level among obese and non-obese individuals using global physical activity questionnaire - M. R., Ramya; Kamath, Vinayak; S., Hemapriya (International Journal Of Community Medicine And Public Health, 2017)
Background: Physical inactivity is considered as a major independent modifiable risk factor for chronic diseases and is one of the most important causes of obesity. Considering the increasing prevalence of chronic diseases in India, the physical activity plays an important role. Taking this into consideration we conducted a study to assess the physical activity levels using the global physical activity questionnaire among obese and non-obese individuals. Methods: A cross sectional study was conducted among adults 20-60 years age-group in rural and urban field practice areas of a medical college in Puducherry by simple random sampling method to select 237 individuals from each area. The level of physical activity was analysed using the global physical activity questionnaire. Results: Among the study population, 61.39% belong to low physical activity level. Among 97 obese individuals, 53.61% belong to low physical activity and no statistical significance was noted between the levels of physical activity and obesity. The prevalence of obesity was 36.13% among those who reported walking and bicycle usage and statistical significance was noted among obese and non-obese individuals (p<0.001). Statistical significant difference was observed in duration of physical activity (minutes/day) among obese and non-obese individuals. Conclusions: The prevalence of obesity seems to be lower among the people who practice simple day-to-day habits such as walking and usage of bicycles as evidenced from our study. Such simple and replicable behavioural modifications need to be brought about at a societal level, if we want to minimise the danger of the looming obesity epidemic.